Head of state immunity under the Rome statute of the International Criminal Court: an analysis of the contemporary legal issues and the African Union's response to the prosecution of African heads of state - Oyugi, Phoebe Akinyi (Rhodes University, Faculty of Law, Law, 2015)
This research examines the impact of head of state immunity on the relationship between Africa and the International Criminal Court (ICC). Thus, it investigates the position of heads of state immunity before international criminal tribunals with special regard to the ICC and assesses the response of African States Parties to the Rome Statute of the International Criminal Court (Rome Statute) to their cooperation obligation under article 98 (1). In addition, it seeks to ascertain the extent to which the African Union (AU) decisions impact on the decision of African States Parties to the Rome Statute to cooperate with the ICC and determine the legality of Article 46 bis of the Protocol on Amendments to the Protocol on the Statute of the African Court of Justice and Human Rights (the Amendment Protocol). Thereafter, it appraises the possible impact of these developments on the application of the principles of international criminal justice in Africa and finally, makes recommendation on ways in which the AU-ICC relationship can be improved. The thesis begins by discussing immunity as a rule of customary international law and the exceptions to its application with regard to international criminal law. This paves way for the analysis of the cooperation regime of the ICC and exceptions thereto with special focus on immunity under article 98 (1) of the Rome Statute. The factors arising from the AU decisions relating to cooperation with the ICC are also discussed with a view to determine their justification under international law. The thesis draws on examples from Chad, Kenya and Malawi to illustrate the manner in which African States Parties to the Rome Statute respond to their cooperation obligation and to what extent this response is affected by the AU position. Lastly, the position of article 46 A bis of the Amendment Protocol, which safeguards immunity based on official capacity, is analysed with a view to determine how the introduction of this new provision is likely to affect the application of international criminal law in the African continent. Drawing on the study of the issues above, the thesis comes to the following conclusions. First, the application of immunity before a particular tribunal depends on the factors influencing its establishment and its mandate as provided for in the constitutive instrument. Secondly, states parties to the Rome Statute can rely on article 98 (1) to deny the ICC request for the arrest and surrender of President Bashir because he is the head of a non-party state. Thirdly, the AU's position does not have a direct impact on the decisions by African States Parties to the Rome Statute on the issue of the arrest and surrender of President Bashir to the ICC. Fourthly, some of the AU grievances against the ICC have justification in international law and therefore deserve the attention of the ICC and the international community. Fifthly, article 46 A bis is in line with the principles of international law on immunities. Given these findings, the thesis recommends that the AU-ICC relationship should be mended in the interest of international criminal justice. And that this can be done by: strengthening the capacity of African States and Africa as a region to deal with international crime occurring in Africa; forging a deeper cooperation between the AU and the United Nations Security Council (UNSC) in ICC related matters; and by the ICC adopting a broad interpretation of its discretion during the prosecution of heads of state. This would allow the ICC to mete out justice without jeopardizing the proper functioning of the states whose heads are on trial.
Keywords: Uncatalogued